The Gambia : First Review of the Staff-Monitored Program and Request for a 39-Month Arrangement under the Extended Credit Facility. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents The Gambia's First Review of the Staff-Monitored Program and Request for a 39-Month Arrangement Under the Extended Credit Facility (ECF). The IMF-supported program aims to help The Gambia to be better prepared for external shocks, pursue high and inclusive growth, lessen debt vulnerabilities, strengthen public financial management, and bolster domestic revenue mobilization. The ECF arrangement is essential to help the authorities deal with the challenges posed by the coronavirus disease 2019 pandemic. The Gambian authorities' commitment to prudent policies and institutional improvements has supported robust economic growth, while voluntary debt service deferrals from their main external creditors have helped attain debt sustainability. The authorities should remain committed to fiscal consolidation in the medium-term to ensure debt sustainability. The vulnerabilities identified in the 2019 Financial Sector Stability Assessment should be addressed to ensure soundness of the financial sector and improve legal and supervisory framework for banking supervision. The authorities should leverage the financial inclusion strategy, including through mobile banking, while strengthening the oversight of nonbanking institutions and monitoring of risks involved in mobile banking.